Psychosocial factors associated with bulimia nervosa during pregnancy: An internal validation study. Issue 6 (27th October 2014) - Watson, Hunna J.; Von Holle, Ann; Knoph, Cecilie; Hamer, Robert M.; Torgersen, Leila; Reichborn‐Kjennerud, Ted; Stoltenberg, Camilla; Magnus, Per; Bulik, Cynthia M.
ABSTRACT Objective The aim of this paper was to internally validate previously reported relations (Knoph Berg et al., Aust N Z J Psychiatry, 42, 396–404, 2008) between psychosocial factors and bulimia nervosa (BN) outcomes during pregnancy. Method This study is based on the Norwegian Mother and Child Cohort Study (MoBa) conducted by the Norwegian Institute of Public Health. Participants were women enrolled during pregnancy (N = 69, 030). Internal validity was evaluated by way of bootstrapped parameter estimates using the overall sample and a split sample calibration approach. Results Bootstrap bias estimates were below the problematic threshold, and extend earlier findings (Knoph Berg et al., Aust N Z J Psychiatry, 42, 396–404, 2008) by providing support for the validity of the models at the population level of all pregnant women in Norway. Bootstrap risk ratios indicated that prevalence, incidence, and remission of BN during pregnancy were significantly associated with psychosocial factors. The split sample procedure showed that the models developed on the training sample did not predict risks in the validation sample. Discussion This study characterizes associations between psychosocial exposures and BN outcomes among pregnant women in Norway. Women with lifetime and current self‐reported psychosocial adversities were at a much higher risk for BN during pregnancy. Psychosocial factors were associated with BN remission during pregnancy, inviting the prospect of enhancing therapeutic interventions. We consider the findings in the context of reproducibility in science. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:654–662)